Stress-strain behavior of remoulded cement-treated Singapore marine clay - Xiao, H. (2014)
Geomechanics and Geotechnics: From Micro to Macro - Proceedings of the International Symposium on Geomechanics and Geotechnics: From Micro to Macro, IS-Shanghai 2010